'The limits of my language': Sense of belonging/otherness of minority teachers in Israel. Issue 1 (22nd March 2023) - Erlich Ron, Rakefet; Gindi, Shahar
Belonging is a basic human experience that symbolizes social relations and social structure. This study examined the institutional sense of belonging of minority teachers to their school and its association with sociodemographic (first language, education and gender) and systemic variables (seniority, heterogeneity of training college, teaching discipline, role at school and education system). We found that sociodemographic variables had a much stronger association to the teachers' sense of belonging than systemic variables did. Particularly, a strong relationship was found between the teachers' sense of belonging and what they defined as their first language. Conversely, most systemic variables had no relation to institutional belonging, except teaching discipline. The findings indicate the difficulties education systems have in incorporating minority teachers or even moderating their sense of otherness by offering the opportunity of recognition of all teachers. We argue that this stems from native language being a core/basic status, whether it is related to immigration or to a national divide.